Higher CCEA GCSE Mathematics Higher - Hamilton, Neill (London, UNKNOWN : Hodder Education, 2017)
Build all the necessary skills to progress your students' learning and develop their problem-solving skills with this fully updated edition of the market-leading Student's Book for CCEA GCSE Mathematics. - Supports you and your students through the new specifications with content mapped to the new module options with material for each module (M1/M5, M2/M6 F or M3/M7 and M4/M8 H) clearly indicated throughout. - Prepares students for assessment with plenty of practice questions divided into calculator and non-calculator, plus links to further relevant and appropriate exam questions.- Develops u.
19 FactorisationCommon factors; Grouping; The difference of two squares; Factorising quadratic expressions; Expressions requiring several methods for factorisation; 20 Algebraic fractions; Simplifying algebraic expressions; Adding and subtracting algebraic fractions; Multiplying and dividing algebraic fractions; 21 Solving quadratic equations; Solving quadratic equations by factorisation; Solving quadratic equations using the quadratic formula; Solving quadratic equations involving algebraic fractions; Using quadratic equations to solve problems; 22 Straight lines and linear graphs.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
Master record variable field(s) change: 072, 082
Keywords: Mathematics -- Examinations, questions, etc; MATHEMATICS / Essays; MATHEMATICS / Pre-Calculus.; MATHEMATICS / Reference; Electronic books